Differentiated Learning Training for Madrasah Ibtidaiyah Teachers - Lestari, Dirga Ayu; Hanifa, Millata; Mutiara, Eka; Adilah, Nida; Mutaqin, Mumu Zainal (STAI Publisistik Thawalib Jakarta, 2025)
The aim of this community service is to enhance the skills and mastery of teachers in applying differentiated learning at state elementary madrasah 1 Cilegon, Banten. The method of community service used is PAR (Participatory Action Research) with the use of an LCD projector, sound system, and educational props to support differentiated learning activities. The results show that the teachers were able to understand and master differentiated learning. This was proven by the results of simulations and practices conducted by the teachers in applying differentiated learning in the Islamic Elementary class. In conclusion, the training session ran smoothly and successfully had a positive impact on improving the competence of the teachers at state elementary madrasah 1 Cilegon.